If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + y) * y = 504 Reorder the terms for easier multiplication: y(3 + y) = 504 (3 * y + y * y) = 504 (3y + y2) = 504 Solving 3y + y2 = 504 Solving for variable 'y'. Reorder the terms: -504 + 3y + y2 = 504 + -504 Combine like terms: 504 + -504 = 0 -504 + 3y + y2 = 0 Factor a trinomial. (-24 + -1y)(21 + -1y) = 0Subproblem 1
Set the factor '(-24 + -1y)' equal to zero and attempt to solve: Simplifying -24 + -1y = 0 Solving -24 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -1y = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -1y = 0 + 24 -1y = 0 + 24 Combine like terms: 0 + 24 = 24 -1y = 24 Divide each side by '-1'. y = -24 Simplifying y = -24Subproblem 2
Set the factor '(21 + -1y)' equal to zero and attempt to solve: Simplifying 21 + -1y = 0 Solving 21 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -1y = 0 + -21 Combine like terms: 21 + -21 = 0 0 + -1y = 0 + -21 -1y = 0 + -21 Combine like terms: 0 + -21 = -21 -1y = -21 Divide each side by '-1'. y = 21 Simplifying y = 21Solution
y = {-24, 21}
| 52x^5y^5-65x^4y^5=0 | | 42a^8-14a^10= | | -bc-cx=-S+bx | | c=200+6x | | 2/3x+15=12 | | 9-8p-1=45 | | 3x+5=x(x-1) | | X^2-5x+5=2x^2+7x+6 | | (2x^3y^3/2)/(x^-.5y^2)^-2 | | y=3sinx-4cos^3x | | 4a+b+4c=9 | | X^2-5=2x^2+7x+6 | | (-27/64)^-2/3 | | n+18+2n=90 | | S=bx-bc+cx | | ((2m^3*n^5)/(4n^3))^4 | | (27x)^(2/3)(3x^(6/5)) | | 5v/9=10 | | 7/2w=42 | | Y=-8+27X+20X^2 | | f(x)=7x/3x-9 | | Y=20X^2+27X-8 | | 7+7x=4(5x+2)-1 | | x+a=a+1 | | 140+2x=-120-11x | | Y=9x^2-9x+2 | | 5a-4=3a+36 | | 2X+25=X+32 | | 7a+7a^2+14b^2= | | x^2+(4k-8)*x-16=0 | | 2n+4=30 | | 3x+3(x-8)=6x-2(x-10) |